"PLATEROS" LATE PRECOLONIAL IN TAMBO DE MORA, CHINCHA VALLEY (AGES XIV - XVI) - Alcalde Gonzáles, Javier (2010)
During the years 1998 and 2001, The Chincha Archaeological Investigations Program, of the Andean Institute of Archaeological Studies – INDEA, has focused part of their investigations in a sector of the monumental complex of Tambo de Mora, composed by a superposition of evidences from metallurgical workshops. These were used to purify and heat the metal, and to making the final products. The use, there were remodelations and redistributions of this space. The analysis indicates that the metallurgical work was concentrated on silver and, probably, gold